REDUCING RISK OF LOW SATURATION GAS IN KUMANG FIELD USING CSEM FORWARD MODELLING - SALLEH, NUR FARHANA (2020)
A key strength of controlled-source electromagnetic (CSEM) in hydrocarbon exploration relies on its method's principle on measuring the contrasting resistivity between the shale and hydrocarbon-bearing sand. This research is conducted to meet the objectives; (a) to model the elastic and electrical rock property and applied in 1D seismic and 1D CSEM modellings to gas saturation and sand thickness variation of the thin-bed reservoirs in Kumang field (b) to model a robust resistivity volume driven by seismic attributes using the predictive method (c) to delineate the lateral CSEM response of the thin-bed reservoirs in Kumang field using 2.5D CSEM forward modelling.